Do not play God: contrasting effects of deontological guilt and pride on decision-making - Mancini, Alessandra; Mancini, Francesco (Frontiers in Psychology, 2015)
Recent accounts support the existence of two distinct feelings of guilt: altruistic guilt, arising from the appraisal of not having been altruistic towards a victim and deontological guilt, emerging from the appraisal of having violated an intuitive moral rule. Neuroimaging data has shown that the two guilt feelings trigger different neural networks, with deontological guilt selectively activating the insula, a brain area involved in the processing of disgust and self-reproach. Thus, insula activation could reflect the major involvement of self-reproach in deontological guilt rather than in altruistic guilt. However, only a few studies have empirically tested whether and how deontological and altruistic guilt differently affect decision making and none have compared enhanced self-worth. Here we asked three groups of participants, respectively induced with either pride, deontological or altruistic guilt, to participate in a third–party version of the ultimatum game in which they were asked to decide on behalf of others to accept or reject economic offers with several degrees of fairness. Results revealed that only deontological participants had higher median acceptances of Moderately Unfair offers as compared to proud participants. However fairness judgments were not different between groups, suggesting that deontological participants’ moral standards had not decreased. Crucially, a higher increase in deontological guilt was associated with an increase in the odds of accepting 30:70 offers. The opposite effects that deontological guilt and pride exert on self-worth can account for these results. Specifically, proud participants felt entitled enough to take action in order to restore equity, while deontological participants followed the “Do not play God” principle, which limited their decisional autonomy, not allowing them to decide on behalf of others.